ЕCОLOGICAL-TECHNOLOGICAL ASPECTS OF PROBLEM OF WASTES - Орфанова, М. М.; Орфанова, М. М.; Пустогов, В. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Urgency of the problem of the accumulation departure is considered іn article. It is accented on that practically all types wastes can be used in sphere production as secondary raw material. Efficiency of the use the method mechanoactivation substance is considered for decision majority ecological tasks, in accordance with wastes salvaging.